Pengaruh Penggunaan Model Kooperatif Tipe TPS Terhadap Hasil Belajar PKn Kelas V Sekolah Dasar - asmeli, rezi; Reinita, Reinita; Fitria, Yanti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
The purpose of this research was to prove the influenceof the use the Cooperatif model types Think Pair Share against results of student learning on the learning of PKn in class V 15 State Primary School Padang Sarai. This type of research was Quasi Experimental Design. The technigue of sampling in research this is a Simple Random Sampling. The data processed by a test of difference (t-test). From the analysis of the test-t in get tacount = 3,08> ttable = 2,000, in significant α 0,05. The result showed that the use of the Cooperative model types Think Pair Share (TPS) effect to the results of student learning on the topic describes the territory of the State Union of Republic of Indonesia (SO) on PKn Subjects in class V 15 State Primary School Padang Sarai. Keywords: Model Think Pair Share, PKn